Preoperative Treatment With Pazopanib in a Case of Chemotherapy‐Resistant Infantile Fibrosarcoma. Issue 2 (16th September 2015) - Yanagisawa, Ryu; Noguchi, Masahiko; Fujita, Kenya; Sakashita, Kazuo; Sano, Kenji; Ogiso, Yoshifumi; Katsuyama, Yoshihiko; Kondo, Yoshiaki; Komori, Kazutoshi; Fujihara, Ikuko; Kitamura, Rei; Hiroma, Takehiko; et al.
Abstract : Clinical and radiological diagnosis of infantile fibrosarcoma (IFS) is challenging because of its similarity to vascular origin tumors. Treatment involves complete resection. Although chemotherapy may allow more conservative resection, treatment guidelines are not strictly defined. One IFS patient with an unresectable tumor had disease progression during chemotherapy. A primary tumor sample showed high VEGFR‐1/2/3 and PDGFR‐α/β expression. After pazopanib therapy, most tumor showed necrosis within 29 days and could be removed completely, with no relapse in 8 months post‐resection. When IFS features hypervascularity, VEGFR and PDGFR expression may be high, thus allowing consideration of VEGFR inhibitors such as pazopanib. Pediatr Blood Cancer © 2015 Wiley Periodicals, Inc.